2013
DOI: 10.3346/jkms.2013.28.8.1226
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Amniotic Infection/Inflammation as a Risk Factor for Subsequent Ruptured Membranes after Clinically Indicated Amniocentesis in Preterm Labor

Abstract: The aim of this study was to determine whether intra-amniotic infection/inflammation (IAI) was associated with subsequent ruptured membranes in women with preterm labor and intact membranes who had a clinically indicated amniocentesis. This retrospective cohort study included 237 consecutive women with preterm labor (20-34.6 weeks) who underwent amniocentesis. The clinical and laboratory parameters evaluated included demographic variables, gestational age, C-reactive protein (CRP) and amniotic fluid (AF) white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 24 publications
(33 reference statements)
1
80
0
Order By: Relevance
“…In particular, sterile IAI can be a preexisting condition or can be either triggered or aggravated by invasive diagnostic procedures such as amniocentesis. Consistently, a recent study [6] suggested that preexisting infection/inflammation may be related to the rupture of membranes following amniocentesis, with the procedure itself possibly contributing to the multifactorial etiology of PPROM. Thus, control of inflammation is essential in order to prevent the risks associated with amniocentesis and other invasive procedures.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In particular, sterile IAI can be a preexisting condition or can be either triggered or aggravated by invasive diagnostic procedures such as amniocentesis. Consistently, a recent study [6] suggested that preexisting infection/inflammation may be related to the rupture of membranes following amniocentesis, with the procedure itself possibly contributing to the multifactorial etiology of PPROM. Thus, control of inflammation is essential in order to prevent the risks associated with amniocentesis and other invasive procedures.…”
Section: Discussionmentioning
confidence: 64%
“…Although the aforementioned complications might have a multifactorial etiology [3], a growing body of evidence suggests that intra-amniotic inflammation and infection, together with invasive diagnostic procedures, such as amniocentesis, may be important factors involved in the onset of pregnancy complications [2, 4, 5]. In this regard, it has recently been observed that a preexisting inflammatory state might predispose pregnant women undergoing amniocentesis to premature rupture of membranes within 48 hours from the procedure [6]. Furthermore, a higher AF concentration of IL-6 had already been reported in women with spontaneous abortion following amniocentesis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal amniocentesis was performed under ultrasound guidance after informed consent was obtained from the patient, and AF was cultured for aerobic and anaerobic bacteria, as well as genital mycoplasma ( Ureaplasma urealyticum and Mycoplasma hominis ) and analyzed for white blood cell (WBC) count, according to methods previously described . The remaining AF was centrifuged and stored at −70°C until assayed.…”
Section: Methodsmentioning
confidence: 99%
“…Following our hospital protocol and previously described methods, the serum C-reactive protein (CRP) levels were measured in all participants at the time of amniocentesis. 18 Medications, such as antibiotics, tocolytics, or corticosteroids, were commenced after sampling.…”
Section: Amniotic Fluid Sample Collection and Preparationmentioning
confidence: 99%